Ficus elastica Leaf Extract Effect Toward IL-10 and TNF-α as a Preeclampsia Model on Hypoxia-induced EA.hy926 - Chrismis Novalinda Ginting; I Nyoman Ehrich Lister; Ermi Girsang; Maya Sari Mutia; Yolanda Eliza Putri Lubis; Annisa Amalia; Wahyu Setia Widodo; Dwi Surya Artie; Rizal Rizal; Wahyu Widowati (Journal of Mathematical and Fundamental Sciences, 2021)
Preeclampsia is a pregnancy complication characterized by proteinuria, hypertension, hypoxia as well an increased systemic inflammatory response. It affects 5 to 10% of all births and is a leading factor in fetal and maternal morbidity and death. Ficus elastica L. leaves are known to have natural compounds with anti-inflammatory and antioxidant properties. This research assessed the potential of F. elastica leaf extract (FEE) as anti-inflammatory agent in a hypoxic-induced human endothelial cell line (EA.hy926) as preeclampsia model. F. elastica leaves were extracted using 70% ethanol. Cytotoxic assay of the FEE in different concentrations (3.13 to 100 µg/ml) against EA.hy926 was done using MTS assay. The FEE’s anti-inflammatory activity was measured with ELISA for the TNF-α and IL-10 parameters. The FEE did not cause cytotoxicity to the EA.hy926 cells, with viability above 80% at the highest concentration. The FEE could decrease the pro-inflammatory TNF-α level and increase the IL-10 level as anti-inflammatory markers in the preeclampsia model at significance level p < 0.05. This study suggests that FEE is a safe alternative herbal medicine for preeclampsia treatment.